Salinity signaled by trapped air bubbles during freezing desalination - Keke Shao; Mengjie Song; Xiaowei Li; Xuan Zhang; Long Zhang; Christopher Yu Hang Chao (Desalination, 2026)

Observer coverage and interaction rates determine the choice between design‐based and machine learning bycatch estimators for rare species - Christopher Long; Robert Ahrens; T. Todd Jones; Zachary Siders (Conservation Biology, 2026)
Robust estimates of the magnitude of protected species bycatch are essential for effective fisheries management and marine conservation. Existing bycatch estimation methods typically struggle to accurately and precisely estimate the bycatch of rare species as a result of the statistical assumptions necessary to overcome infrequent encounters and, often, low observer coverage. We compared the widely used Horvitz–Thompson design‐based estimator with a machine learning framework for estimating protected species bycatch based on ensemble random forests. We simulated reduced observer coverage in the 100% observed Hawaii shallow‐set pelagic longline fishery and compared the two estimation methods for five species: oceanic whitetip sharks ( Carcharhinus longimanus ), Laysan albatross ( Phoebastria immutabilis ), black‐footed albatross ( Phoebastria nigripes ), loggerhead sea turtles ( Caretta caretta ), and leatherback sea turtles ( Dermochelys coriacea ). Machine learning‐based estimates were more precise than design‐based estimates for all species, but annual and long‐term accuracy varied with bycatch rates and spatial clustering of interactions. The machine learning approach improved the precision of bycatch estimates for oceanic whitetip sharks (3.5% of sets with interaction) without reducing long‐term accuracy. As interaction rates declined below this level, the ensemble random forests method introduced increasing bias and resulted in a preference for the design‐based estimator in real‐world applications. The ensemble random forests approach relaxed the trade‐off between accurate, precise bycatch estimates and observer coverage for species with greater than 3% interaction rates. However, high observer coverage remains irreplaceable for effectively estimating bycatch for the rarest species, and the imprecision of design‐based estimates should be accounted for in management decisions.

Comparative toxicity of bisphenol A and analogues to the marine polychaete Arenicola marina: Another case of regrettable substitutes? - Paula Milliken; Anais Ansari; Jon Barry; Ioanna Katsiadaki; Melinda Long; Sara Losada; Christopher Martin; Lara Pearson; Marta Vannoni; Alex R.O. Cousins (Marine Pollution Bulletin, 2026)

Short-term mechanisms, long-term consequences: transcriptomic insights into ocean acidification tolerance and stress in juvenile snow crab - Laura H. Spencer; Ingrid Spies; Jennifer L. Gardner; Steven B. Roberts; W. Christopher Long (Frontiers in Marine Science, 2026)
Understanding how marine species tolerate ocean acidification (OA) is critical for predicting biological responses to ocean change, as well as impacts on the ecosystems and industries that rely upon them. Snow crab ( Chionoecetes opilio ) are both a major fishery resource in the Bering Sea and an important component of high-latitude marine food webs. Experimental work suggests that snow crab are relatively tolerant of OA, but that this tolerance has limits. In a recent study, juveniles maintained growth and molting during a year-long exposure to moderate OA (pH 7.8) and severe OA (pH 7.5), while survival declined in the severe OA treatment after 250 days. In this companion study, we applied RNA-seq to characterize transcriptomic responses to OA using individual whole-body juvenile snow crab. Expression profiles were characterized in OA treatments (pH 7.8, pH 7.5) at two time points: after 8 hours to identify molecular mechanisms underlying short-term tolerance; and after 88 days to understand chronic effects of severe OA (10–14 crabs per treatment and time point). The 8 h transcriptional response involved strong activation of genes associated with mitochondrial protein repair, cuticle maintenance, and immune modulation, processes shared between OA treatments but of substantially greater magnitude under severe OA (616 versus 148 differentially expressed genes). After 88 days of OA exposure, differential expression among the two OA treatments (186 genes) revealed sustained upregulation of stress- and damage-mitigation pathways in severe OA (pH 7.5). These findings suggest that juvenile snow crab tolerate OA through flexible molecular responses that maintain energy production capacity, cellular, and protective barrier function. However, persistent activation of these pathways under severe OA indicates a chronic stress state that precedes outward physiological effects and likely contributes to increased mortality under long-term exposure. We further highlight potential early indicators of chronic acidification stress in snow crab, among which a gene likely coding for carbonic anhydrase 7 (CA7) appears to be the most promising biomarker candidate.

Huron Chipper a Broadly Adapted Chip-Processing Variety with Long-Term Storage Potential and Resistance to Late Blight and Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2026)
Huron Chipper is a high yielding round white chip-processing variety with resistance to late blight ( Phytophthora infestans ) and tolerance to common scab ( Streptomyces scabies ). Selected from a cross between the Michigan State University breeding lines MSQ070-1 and MSR156-7, it was designated MSW485-2 during its initial evaluation and development. Huron Chipper is high yielding and broadly adapted, showing equal or better agronomic performance compared to Snowden in all major growing regions in the United States. In on-farm trials in Michigan and national SNAC trials, Huron Chipper had higher total and marketable yields and specific gravity (1.083 in Michigan, 1.088 on average nationally) compared to Snowden. Formally released in 2018, Huron Chipper offers producers an agronomically competitive alternative to Snowden and Atlantic with better resistance to common scab, late blight, and blackspot bruise with high chip-processing quality up to eight months post-harvest.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Innovative In Vitro-In Silico Platform for Dose–Response Modeling in Canine Bladder Cancer: A 3D Organoid- and Mathematics-Based Approach - Mackenzie Long; Yvonne Peng; Saumya Gade; Hannah Nicholson; Michael Catucci; Christopher Zdyrski; Aleksandra Pawlak; Megan Corbett; Corey Saba; Travis Laver; Emily Rawlings; Maria Orbay-Cerrato; et al. (The AAPS Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Enhanced MPM framework with multipatch isogeometric analysis for geotechnical applications - Abdelrahman Alsardi; Alba Yerro; Christopher Curtis Long (Computers and Geotechnics, 2026)

Ocean acidification reduces juvenile snow crab, Chionoecetes opilio, survival but does not affect growth or morphometrics - W. Christopher Long (Journal of Experimental Marine Biology and Ecology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Medically Tailored Grocery Delivery for Food Pantry Clients with Diabetes - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Brett Rowland; Bonnie Faitak; Jazmin Lane; Rosana Solis-Garcia; Holly C. Felix; Krista Langston; Pearl A. McElfish; Juan Mejia-Otera; et al. (Journal of Nutrition Education and Behavior, 2025)

Ultrasound accelerates zeolite synthesis: Predictive modelling via machine learning - Deborah Braide; Eslam G. Al-Sakkari; Christopher Panaritis; Long Zhe Li; Ntumba Kabongo Etienne; Laura Lavigne; Alexander Abanobi; Ahmed Ragab; Gregory Patience; Daria Camilla Boffito (Journal of Environmental Chemical Engineering, 2025)

Superior degradation of endocrine disruptors over defective iron pyrites assisted by vacancy-induced disassociation of hydrogen peroxide - Han-Liang Fang; Yu-Hang Xu; Xiang-Min Jin; Hao-Ran Long; Wen-Ni Zhang; Han-Hui You; Zhou Zhong; Yi-Dong Hou; Hai-Lei Cao; Christopher Rensing; Jian Lü (Chemical Engineering Journal, 2025)

Ecological risk assessment for Cry1Da_7, Cry1B.3 and Vip3Cb1 proteins expressed in MON 89151 cotton: an insect-protected cotton with targeted activity against Lepidoptera - Harit K. Bal; Collin J. Preftakes; Lawrence Long; Carlos J. Esquivel; Frankie Stubbins; Chitvan Khajuria; Jianguo Tan; David Dyck; Brent Werner; Justin Ungerer; Bingyao Li; Yu Liu-Gontarek; et al. (Transgenic Research, 2025)

Blackberry, an Attractive Deep Purple Potato Variety with Resistance to Common Scab and Extreme Resistance to Potato Virus Y - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Tomás D. Lopes; Joseph I. Ulasi; Christopher M. Long (American Journal of Potato Research, 2025)
Blackberry is a tablestock variety with uniquely deep purple skin and flesh. The tubers have an attractive, uniform, round shape with common scab resistance and low incidence of internal defects. It also carries the Rysto marker for extreme resistance to potato virus Y. When baked or microwaved, the tuber flesh is a brilliant deep purple with an enjoyable mild taste. It was selected in 2011 from a cross between two breeding lines COMN07-W112BG1 and MSU200-5PP. Although primarily oriented towards the fresh market, Blackberry is an all-purpose variety that also has the ability to chip out of the field. Yields are high under irrigated conditions and specific gravity averaged 1.068 in on-farm trials in Michigan.

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

Petoskey A High Gravity Chip-Processing Variety with Long-term Storage Potential and Resistance to Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Petoskey is a high specific gravity round white chip-processing potato variety with resistance to common scab ( Streptomyces scabies ). It was selected from a cross between Beacon Chipper and the breeding line MSG227-2, and designated MSV030-4 during the trialling phase of its development. This variety has high yield potential with attractive round, uniform tubers with netted skin. Five years of field testing in Michigan demonstrate that yield of Petoskey is similar to Snowden with higher specific gravity averaging 1.089. Out-of-the field chip scores were comparable to Snowden while Petoskey chip scores outperform Snowden in long-term storage trials at eight months post-harvest. Petoskey has a medium upright canopy and a mid to full season maturity with excellent long-term storage chip-processing quality. This variety has performed well in Michigan in on-farm trials and multistate national SNAC trials. Formally released in 2019, Petoskey is a comparable alternative to Snowden with strong resistance to common scab. Producers can expect higher specific gravity and longer storage potential than Snowden with high chip-processing quality up to eight months post-harvest.

Mackinaw: A Round White Potato Variety with Excellent Long-Term Storage Chip-Processing Quality and Resistance To Late Blight, Potato Virus Y, Golden Cyst Nematode and Tolerance To Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Jaime Willbur; Christopher M. Long (American Journal of Potato Research, 2025)
Mackinaw is a disease resistant round white chip-processing potato with resistance to potato virus Y (PVY), late blight ( Phytophthora infestans ), and tolerance to common scab ( Streptomyces scabies ). Mackinaw also carries the TG689 marker for the H1 resistance gene to golden cyst nematode ( Globodera rostochiensis ) race Ro1. Designated as MSX540-4 during the trialling phase of its development, it was selected from a cross between the cultivars Saginaw Chipper and Lamoka. Field testing in Michigan show that this variety has average yield potential, similar to Snowden, with high specific gravity averaging 1.087. Mackinaw has a strong vine with a mid- to late-season maturity, producing a large percentage of A-sized tubers with a low incidence of internal defects and excellent long-term storage chip-processing quality. Mackinaw performed well in on-farm trials in Michigan and in multistate SNAC trials showing broad adaptation, especially in the northern tier states. Formally released in 2017, Mackinaw offers a unparalleled combination of disease resistance, long-term storage potential, and excellent chip-processing quality out of the field and out of long-term storage.

Identifying and reducing climate uncertainty in fisheries management reference points - André E. Punt; Michael G. Dalton; W. Christopher Long; Wei Cheng; Albert J. Hermann; Kirstin K. Holsman (Fisheries Research, 2025)

Diet Quality Among Community Members With Diabetes and Food Insecurity in Northwest Arkansas: Comparison Across 3 Racial/Ethnic Groups - Eliza Short; Ji Li; James P. Selig; Kelsey Bounds; Alexandra Diaz-Cruz; Brett Rowland; Holly C. Felix; Krista Langston; Pearl A. McElfish; Christopher R. Long (Journal of Nutrition Education and Behavior, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Environmental contamination predicts mammal diversity and mesocarnivore activity in the Seattle-Tacoma metro area - Yasmine Hentati; Cesar O. Estien; Zachary Hawn; Mark J. Jordan; Robert A. Long; Rachael Mueller; Katie R. Remine; Laura R. Prugh; Christopher J. Schell (Urban Ecosystems, 2025)

Commentary: Synthesis of thresholds of ocean acidification impacts on decapods - Nina Bednaršek; Richard F. Ambrose; Piero Calosi; Richard A. Feely; Steven Y. Litvin; W. Christopher Long; John I. Spicer; Jasna Štrus; Fayçal Kessouri; Martha Sutula; Stephen B. Weisberg (Frontiers in Marine Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Bitter crab disease dynamics in eastern Bering Sea Tanner and snow crab: An underestimated and emergent stressor - Erin J. Fedewa; Pamela C. Jensen; Hamish J. Small; Michael A. Litzow; Michael J. Malick; Leah S. Zacher; W. Christopher Long; Stan Kotwicki (Fisheries Research, 2025)

Do economic trade-offs matter in climate policy support? Survey evidence from the United Kingdom and Australia - Christopher Bell; Ekaterina Rhodes; Zoe Long; Colette Salemi (Energy Policy, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

TracMyAir smartphone application for modeling exposures to PM2.5 and ozone – Integration with air quality networks and location-activity sensors - Michael Breen; Vlad Isakov; Catherine Seppanen; Saravanan Arunachalam; Miyuki Breen; Steven Prince; Thomas Long; David Heist; Parikshit Deshmukh; K. Wyat Appel; Christian Hogrefe; Benjamin Murphy; et al. (Science of The Total Environment, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Magmatic N2 degassing dominates nitrogen loss during sediment subduction and granitoid genesis - Yunzhe Chen; Peng Wu; Tiago Angelo; Christopher Spencer; Long Li (Earth and Planetary Science Letters, 2024)

A quantitative assessment of (bacterio)chlorophyll assignments in the cryo-EM structure of the Chloracidobacterium thermophilum reaction center - Christopher J. Gisriel; David A. Flesher; Zhuoran Long; Jinchan Liu; Jimin Wang; Donald A. Bryant; Victor S. Batista; Gary W. Brudvig (Photosynthesis Research, 2024)

Self-reported previous experiences with sharks and stingrays predict behavioral intentions of tolerance: differential effects of wild versus captive marine predators - Gabriella M. Hancock; Katie D. Dudley; Dede Long; Christopher G. Lowe (Frontiers in Marine Science, 2024)
Previous research has shown that the general population are more likely to learn about certain species groups (such as sharks) from popular media as opposed to their own first-hand experience. Yet, personal encounters with these animals can drastically affect people’s beliefs and behaviors. This study surveyed 380 members of the public to assess their previous experience of encountering sharks and stingrays in the wild as well as at zoos and aquaria, and tested how said experiences influenced their behavioral intentions of tolerance for these particular elasmobranchs. Results indicated that self-reported experience having previously encountered these species groups in the wild was predictive of all assessed behavioral indicators of tolerance for sharks and rays. Self-reported previous encounters with captive animals were predictive of fewer behavioral intentions of tolerance, and only for the tolerance of sharks. Findings reveal the important role that first-hand interaction with these animals plays in humans’ tolerance to coexist and care for these animals and their habitat. Implications for conservation are discussed.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Red king crab larval survival and development are resilient to ocean acidification - W. Christopher Long; Alexandra L. Conrad; Jennifer L. Gardner; Robert J. Foy (Journal of Experimental Marine Biology and Ecology, 2024)

City divided: Unveiling family ties and genetic structuring of coyotes in Seattle - Samantha E. S. Kreling; Ellen M. Reese; Olivia M. Cavalluzzi; Natalee B. Bozzi; Riley Messinger; Christopher J. Schell; Robert A. Long; Laura R. Prugh (Molecular Ecology, 2024)
Linear barriers pose significant challenges for wildlife gene flow, impacting species persistence, adaptation, and evolution. While numerous studies have examined the effects of linear barriers (e.g., fences and roadways) on partitioning urban and non‐urban areas, understanding their influence on gene flow within cities remains limited. Here, we investigated the impact of linear barriers on coyote ( Canis latrans ) population structure in Seattle, Washington, where major barriers (i.e., interstate highways and bodies of water) divide the city into distinct quadrants. Just under 1000 scats were collected to obtain genetic data between January 2021 and December 2022, allowing us to identify 73 individual coyotes. Notably, private allele analysis underscored limited interbreeding among quadrants. When comparing one quadrant to each other, there were up to 16 private alleles within a single quadrant, representing nearly 22% of the population allelic diversity. Our analysis revealed weak isolation by distance, and despite being a highly mobile species, genetic structuring was apparent between quadrants even with extremely short geographic distance between individual coyotes, implying that Interstate 5 and the Ship Canal act as major barriers. This study uses coyotes as a model species for understanding urban gene flow and its consequences in cities, a crucial component for bolstering conservation of rarer species and developing wildlife friendly cities.

Optimizing release strategies for red king crab stock enhancement: Effects of release timing - William Christopher Long; Benjamin J. Daly; Peter A. Cummiskey (Fisheries Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Yield has minimal effect on whole-grain mineral density of modern soft wheat compared to production environment, genotype, and test weight - Curtis B. Adams; Ryan Graebner; Juliet Marshall; Clark Neely; Dan S. Long; Catherine L. Reardon; Christopher W. Rogers (Field Crops Research, 2024)

A machine learning approach for protected species bycatch estimation - Christopher A. Long; Robert N. M. Ahrens; T. Todd Jones; Zachary A. Siders (Frontiers in Marine Science, 2024)
Introduction Monitoring bycatch of protected species is a fisheries management priority. In practice, protected species bycatch is difficult to precisely or accurately estimate with commonly used ratio estimators or parametric, linear model-based methods. Machine-learning algorithms have been proposed as means of overcoming some of the analytical hurdles in estimating protected species bycatch. Methods Using 17 years of set-specific bycatch data derived from 100% observer coverage of the Hawaii shallow-set longline fishery and 25 aligned environmental predictors, we evaluated a new approach for protected species bycatch estimation using Ensemble Random Forests (ERFs). We tested the ability of ERFs to predict interactions with five protected species with varying levels of bycatch in the fishery and methods for correcting these predictions using Type I and Type II error rates from the training data. We also assessed the amount of training data needed to inform a ERF approach by mimicking the sequential addition of new data in each subsequent fishing year. Results We showed that ERF bycatch estimation was most effective for species with greater than 2% interaction rates and error correction improved bycatch estimates for all species but introduced a tendency to regress estimates towards mean rates in the training data. Training data needs differed among species but those above 2% interaction rates required 7-12 years of bycatch data. Discussion Our machine learning approach can improve bycatch estimates for rare species but comparisons are needed to other approaches to assess which methods perform best for hyperrare species.

Development of a nature-based solution for mitigation of Pacific oyster summer mortality: use of the intertidal zone to improve resilience to environmental stressors - Clara L. Mackenzie; Monique R. Raap; Sarah Leduc; Chen Yin V. Walker; Timothy J. Green; Eliah Kim; Emaline M. Montgomery; Sierra L. M. Gray; Amy Long; Christopher M. Pearce (Frontiers in Marine Science, 2024)
In recent years, Pacific oyster growers in British Columbia (BC), Canada have experienced devastating losses due to summer mortality syndrome. While anecdotal evidence suggests that intertidally-grown oysters may fare better during mass mortality events than deep-water counterparts, there remains a lack of research examining how different culture conditions may influence severity. To address this, we compared growth, condition, histopathology, reproductive status, and survival between intertidally- and deep-water-cultured oysters over 2 years at three oyster farms in Baynes Sound (BC). A reciprocal transplant was carried out after 1 year to test the use of the intertidal as a mechanism for promotion of physiological resilience prior to deep-water deployment. Field trial results showed significantly higher final survival in oysters transferred from the intertidal to deep water (83.5%) compared to those maintained in deep water (63.6%), but only at one farm, likely as a consequence of varying physical and/or biological characteristics associated with particular farm locations. Histopathology showed little role of disease with regards to varying survival among treatments, though higher occurrence of Viral Gametocytic Hypertrophy was observed in Year 1 oysters under deep-water (62.2%) versus intertidal (37.8%) conditions. Additionally, after 2 years, there was no significant difference in oyster size nor condition index between oysters transplanted from the intertidal to deep water and those solely cultured in deep water. A laboratory-challenge experiment determined significantly different survival curves of Year 1 intertidally- and deep-water-cultured oysters under immersion/emersion and warming conditions, with final survival of 88% and 64%, respectively, under conditions of high temperature (25°C) and immersion. Likewise, Year 2 (i.e. post-transfer) intertidally- and deep-water-cultured oysters showed significantly different survival curves under laboratory-based Vibrio challenge conditions (16°C) with final survival of 63% and 34%, respectively. Results suggest that partial culture in the intertidal at some farms may be an effective method for conferring resilience to summer mortality in Pacific oysters.

Potential of dynamic ocean management strategies for western Pacific leatherback sea turtle bycatch mitigation in New Zealand - Zachary A. Siders; Campbell Murray; Charity Puloka; Shelton Harley; Clinton Duffy; Christopher A. Long; Robert N. M. Ahrens; T. Todd Jones (Frontiers in Marine Science, 2024)
Western Pacific leatherback sea turtles ( Dermochelys coriacea ) are a priority bycatch mitigation concern due to the projected extinction of the population before the end of the 21st century. The species regularly occurs as bycatch in gillnet and surface longline fisheries. Here, we explore the potential for dynamic ocean management in an emerging hotspot of leatherback sea turtle bycatch in the New Zealand pelagic longline fishery. We compared spatial areas of different sizes built from single oceanographic covariates as well as built from a composite risk surface developed through ensemble random forests. We found that, individually, the Okubo–Weiss parameter, sea surface temperature (SST) anomaly, SST, moon phase, and distance to the SST front were important oceanographic covariates for leatherback sea turtle bycatch. However, the spatial areas built from the composite risk surface were the most effective at discriminating sets with and without bycatch across a range of risk cutoffs. When we also considered implementation metrics of spatial area and coherence as part of performance, the area derived from the composite risk surface with a risk of interaction per set greater than 52% performed best. This spatial area was ephemeral, occurring 1 or 2 weeks each year, and localized, occurring along the north coast of East Cape in the North Island of New Zealand. The apparent presence of discrete spatial areas with elevated risk may be useful to inform future management in the area. Considering implementation metrics in defining utility was useful for identifying tradeoffs between the total size and the underlying covariates delineating a spatial area. As such, we recommend these types of metrics to be included when designing spatial bycatch mitigation strategies elsewhere.

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Functional diversity affects tree vigor, growth, and mortality in mixed-conifer/hardwood forests in California, U.S.A, in the absence of fire - Christopher E. Looney; Jonathan W. Long; Christopher J. Fettig; Jeremy S. Fried; Katherine E.A. Wood; Jackson P. Audley (Forest Ecology and Management, 2023)

An etiological examination of behavioral intentions to support shark and stingray conservancy: the effects of beliefs in elasmobranchs’ cognitive and affective capacities - Gabriella M. Hancock; Katie D. Dudley; Dede Long; Christopher G. Lowe (Frontiers in Marine Science, 2023)
Keystone species populations, including shark and ray taxonomic groups, are declining due to numerous threats. A better understanding of how individual belief structures inform pro-conservation behavioral intentions is therefore critical to foster support for their conservation and the greater biodiversity of world ecosystems. This study conducted a survey to establish the general public’s cognitive beliefs about the mental and affective capacities of two species groups (sharks and stingrays) known to cause injury to humans, and their effects on different behavioral intentions to support their conservation. Results revealed that a range of different behavioral intentions to support animal conservation are driven by a complex interplay of cognitive beliefs, and some effects were specific to a particular species group while others were not. Beliefs in animals’ cognitive awareness and their emotional abilities were predictive of individuals’ self-reported desire to learn more about the animals and their conservation. Beliefs in animals’ cognitive and emotional capacities were predictive of supporting conservation in terms of voting and donating to their conservation. Finally, beliefs in animals’ reasoning abilities were predictive of different behavioral expressions of tolerance, and support for their conservation via voting only. Despite the potential injurious capabilities of these species, these findings have important implications for educational and conservation programs to emphasize or modify specific beliefs in order to facilitate particular pro-conservation behaviors for maximum benefits to conservation efforts.

Adult snow crab, Chionoecetes opilio, display body-wide exoskeletal resistance to the effects of long-term ocean acidification - Tait Algayer; Ahmed Mahmoud; Sanjana Saksena; W. Christopher Long; Katherine M. Swiney; Robert J. Foy; Brittan V. Steffel; Kathryn E. Smith; Richard B. Aronson; Gary H. Dickinson (Marine Biology, 2023)

A replication of the personal-ambient PM2.5 meta-correlation - Steven R. Boomhower; Julie E. Goodman; Christopher M. Long; Tatiana D. Manidis (Environmental Pollution, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Conspecific cues, not starvation, mediate barren urchin response to predation risk - Christopher J. Knight; Robert P. Dunn; Jeremy D. Long (Oecologia, 2022)

Senolytic treatment rescues blunted muscle hypertrophy in old mice - Cory M. Dungan; Vandre C. Figueiredo; Yuan Wen; Georgia L. VonLehmden; Christopher J. Zdunek; Nicholas T. Thomas; C. Brooks Mobley; Kevin A. Murach; Camille R. Brightwell; Douglas E. Long; Christopher S. Fry; Philip A. Kern; et al. (GeroScience, 2022)
With aging, skeletal muscle plasticity is attenuated in response to exercise. Here, we report that senescent cells, identified using senescence-associated β-galactosidase (SA β-Gal) activity and p21 immunohistochemistry, are very infrequent in resting muscle, but emerge approximately 2 weeks after a bout of resistance exercise in humans. We hypothesized that these cells contribute to blunted hypertrophic potential in old age. Using synergist ablation-induced mechanical overload (MOV) of the plantaris muscle to model resistance training in adult (5–6-month) and old (23–24-month) male C57BL/6 J mice, we found increased senescent cells in both age groups during hypertrophy. Consistent with the human data, there were negligible senescent cells in plantaris muscle from adult and old sham controls, but old mice had significantly more senescent cells 7 and 14 days following MOV relative to young. Old mice had blunted whole-muscle hypertrophy when compared to adult mice, along with smaller muscle fibers, specifically glycolytic type 2x + 2b fibers. To ablate senescent cells using a hit-and-run approach, old mice were treated with vehicle or a senolytic cocktail consisting of 5 mg/kg dasatinib and 50 mg/kg quercetin (D + Q) on days 7 and 10 during 14 days of MOV; control mice underwent sham surgery with or without senolytic treatment. Old mice given D + Q had larger muscles and muscle fibers after 14 days of MOV, fewer senescent cells when compared to vehicle-treated old mice, and changes in the expression of genes (i.e., Igf1 , Ddit4 , Mmp14 ) that are associated with hypertrophic growth. Our data collectively show that senescent cells emerge in human and mouse skeletal muscle following a hypertrophic stimulus and that D + Q improves muscle growth in old mice.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Synthesis of Thresholds of Ocean Acidification Impacts on Decapods - Nina Bednaršek; Richard Ambrose; Piero Calosi; Richard K. Childers; Richard A. Feely; Steven Y. Litvin; W. Christopher Long; John I. Spicer; Jasna Štrus; Jennifer Taylor; Faycal Kessouri; Miranda Roethler; et al. (Frontiers in Marine Science, 2021)
Assessing decapod sensitivity to regional-scale ocean acidification (OA) conditions is limited because of a fragmented understanding of the thresholds at which they exhibit biological response. To address this need, we undertook a three-step data synthesis: first, we compiled a dataset composed of 27,000 datapoints from 55 studies of decapod responses to OA. Second, we used statistical threshold analyses to identify OA thresholds using pH as a proxy for 13 response pathways from physiology to behavior, growth, development and survival. Third, we worked with the panel of experts to review these thresholds, considering the contributing datasets based on quality of the study, and assign a final thresholds and associated confidence scores based on quality and consistency of findings among studies. The duration-dependent thresholds were within a pH range from 7.40 to 7.80, ranging from behavioral and physiological responses to mortality, with many of the thresholds being assigned medium-to-high confidence. Organism sensitivity increased with the duration of exposure but was not linked to a specific life-stage. The thresholds that emerge from our analyses provide the foundation for consistent interpretation of OA monitoring data or numerical ocean model simulations to support climate change marine vulnerability assessments and evaluation of ocean management strategies.

Discovery of structural deletions in breast cancer predisposition genes using whole genome sequencing data from > 2000 women of African-ancestry - Zhishan Chen; Xingyi Guo; Jirong Long; Jie Ping; Bingshan Li; Mary Kay Fadden; Thomas U. Ahearn; Daniel O. Stram; Xiao-Ou Shu; Guochong Jia; Jonine Figueroa; Robertson Adjei; et al. (Human Genetics, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Effects of ocean acidification on young-of-the-year golden king crab (Lithodes aequispinus) survival and growth - W. Christopher Long; Katherine M. Swiney; Robert J. Foy (Marine Biology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Rapid assessment of management options for promoting stock rebuilding in data‐poor species under climate change - Jonathan C. P. Reum; P. Sean McDonald; W. Christopher Long; Kirstin K. Holsman; Lauren Divine; David Armstrong; Jan Armstrong (Conservation Biology, 2020)
The development of species recovery plans requires considering likely outcomes of different management interventions, but the complicating effects of climate change are rarely evaluated. We examined how qualitative network models (QNMs) can be deployed to support decision making when data, time, and funding limitations restrict use of more demanding quantitative methods. We used QNMs to evaluate management interventions intended to promote the rebuilding of a collapsed stock of blue king crab (Paralithodes platypus) (BKC) around the Pribilof Islands (eastern Bering Sea) to determine how their potential efficacy may change under climate change. Based on stakeholder input and a literature review, we constructed a QNM that described the life cycle of BKC, key ecological interactions, potential climate‐change impacts, relative interaction strengths, and uncertainty in terms of interaction strengths and link presence. We performed sensitivity analyses to identify key sources of prediction uncertainty. Under a scenario of no climate change, predicted increases in BKC were reliable only when stock enhancement was implemented in a BKC hatchery‐program scenario. However, when climate change was accounted for, the intervention could not counteract its adverse impacts, which had an overall negative effect on BKC. The remaining management scenarios related to changes in fishing effort on BKC predators. For those scenarios, BKC outcomes were unreliable, but climate change further decreased the probability of observing recovery. Including information on relative interaction strengths increased the likelihood of predicting positive outcomes for BKC approximately 5–50% under the management scenarios. The largest gains in prediction precision will be made by reducing uncertainty associated with ecological interactions between adult BKC and red king crab (Paralithodes camtschaticus). Qualitative network models are useful options when data are limited, but they remain underutilized in conservation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Leveraging community-based participatory research capacity to recruit Pacific Islanders into a genetics study - Pearl A. McElfish; Marie-Rachelle Narcisse; Christopher R. Long; Britni L. Ayers; Nicola L. Hawley; Nia Aitaoto; Sheldon Riklon; L. Joseph Su; Shumona Z. Ima; Ralph O. Wilmoth; Thomas K. Schulz; Susan Kadlubar (Journal of Community Genetics, 2017)

Upper thermal tolerance in red and blue king crab: sublethal and lethal effects - W. Christopher Long; Benjamin Daly (Marine Biology, 2017)

Polymeric Nanofiber/Antifungal Formulations Using a Novel Co-extrusion Approach - Mohammad Mofidfar; Jia Wang; Lisa Long; Christopher L. Hager; Chairut Vareechon; Eric Pearlman; Eric Baer; Mahmoud Ghannoum; Gary E. Wnek (AAPS PharmSciTech, 2017)

Distribution and Drivers of a Widespread, Invasive Wetland Grass, Phragmites australis, in Wetlands of the Great Salt Lake, Utah, USA - A. Lexine Long; Karin M. Kettenring; Charles P. Hawkins; Christopher M. U. Neale (Wetlands, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Long-range fine particulate matter from the 2002 Quebec forest fires and daily mortality in Greater Boston and New York City - Ke Zu; Ge Tao; Christopher Long; Julie Goodman; Peter Valberg (Air Quality, Atmosphere & Health, 2016)

Heterotrophic bacteria from an extremely phosphate‐poor lake have conditionally reduced phosphorus demand and utilize diverse sources of phosphorus - Mengyin Yao; Felix J. Elling; CarriAyne Jones; Sulung Nomosatryo; Christopher P. Long; Sean A. Crowe; Maciek R. Antoniewicz; Kai‐Uwe Hinrichs; Julia A. Maresca (Environmental Microbiology, 2016)
Summary Heterotrophic P roteobacteria and A ctinobacteria were isolated from L ake M atano, I ndonesia, a stratified, ferruginous (iron‐rich), ultra‐oligotrophic lake with phosphate concentrations below 50 nM. Here, we describe the growth of eight strains of heterotrophic bacteria on a variety of soluble and insoluble sources of phosphorus. When transferred to medium without added phosphorus ( P ), the isolates grow slowly, their RNA content falls to as low as 1% of cellular dry weight, and 86–100% of the membrane lipids are replaced with amino‐ or glycolipids. Similar changes in lipid composition have been observed in marine photoautotrophs and soil heterotrophs, and similar flexibility in phosphorus sources has been demonstrated in marine and soil‐dwelling heterotrophs. Our results demonstrate that heterotrophs isolated from this unusual environment alter their macromolecular composition, which allows the organisms to grow efficiently even in their extremely phosphorus‐limited environment.

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Do brain cancer rates correlate with ambient exposure levels of criteria air pollutants or hazardous air pollutants (HAPs)? - Peter A. Valberg; Christopher M. Long (Air Quality, Atmosphere & Health, 2012)

Climate Forcing and Salinity Variability in Chesapeake Bay, USA - Jiangtao Xu; Wen Long; Jerry D. Wiggert; Lyon W. J. Lanerolle; Christopher W. Brown; Raghu Murtugudde; Raleigh R. Hood (Estuaries and Coasts, 2012)

Calcium addition at the Hubbard Brook Experimental Forest increases the capacity for stress tolerance and carbon capture in red spruce (Picea rubens) trees during the cold season - Paul G. Schaberg; Rakesh Minocha; Stephanie Long; Joshua M. Halman; Gary J. Hawley; Christopher Eagar (Trees, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Engineered antifouling microtopographies: mapping preferential and inhibitory microenvironments for zoospore attachment - Christopher J. Long; John A. Finlay; Maureen E. Callow; James A. Callow; Anthony B. Brennan (Biofouling, 2010)

Engineered antifouling microtopographies: the role of Reynolds number in a model that predicts attachment of zoospores of Ulva and cells of Cobetia marina - Chelsea M. Magin; Christopher J. Long; Scott P. Cooper; Linnea K. Ista; Gabriel P. López; Anthony B. Brennan (Biofouling, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

A model that predicts the attachment behavior of Ulva linza zoospores on surface topography - Christopher J. Long; James F. Schumacher; Paul A.C. Robinson; John A. Finlay; Maureen E. Callow; James A. Callow; Anthony B. Brennan (Biofouling, 2010)

Isolation and characterization of a magnetotactic bacterial culture from the Mediterranean Sea - Christopher T. Lefèvre; Alain Bernadac; Kui Yu‐Zhang; Nathalie Pradel; Long‐Fei Wu (Environmental Microbiology, 2009)
Summary The widespread magnetotactic bacteria have the peculiar capacity of navigation along the geomagnetic field. Despite their ubiquitous distribution, only few axenic cultures have been obtained worldwide. In this study, we reported the first axenic culture of magnetotactic bacteria isolated from the Mediterranean Sea. This magneto‐ovoid strain MO‐1 grew in chemically defined O 2 gradient minimal media at the oxic–anoxic transition zone. It is phylogenetically related to Magnetococcus sp. MC‐1 but might represent a novel genus of Proteobacteria . Pulsed‐field gel electrophoresis analysis indicated that the genome size of the MO‐1 strain is 5 ± 0.5 Mb, with four rRNA operons. Each cell synthesizes about 17 magnetosomes within a single chain, two phosphorous‐oxygen‐rich globules and one to seven lipid storage granules. The magnetosomes chain seems to divide in the centre during cell division giving rise to two daughter cells with an approximately equal number of magnetosomes. The MO‐1 cell possesses two bundles of seven individual flagella that were enveloped in a unique sheath. They swam towards the north pole with a velocity up to 300 μm per second with frequent change from right‐hand to left‐hand helical trajectory. Using a magneto‐spectrophotometry assay we showed that MO‐1 flagella were powered by both proton‐motive force and sodium ion gradient, which is a rare feature among bacteria.

Hypoxia in Chesapeake Bay Tributaries: Worsening effects on Macrobenthic Community Structure in the York River - William Christopher Long; Rochelle Diane Seitz (Estuaries and Coasts, 2009)

Characterization of a homogeneous taxonomic group of marine magnetotactic cocci within a low tide zone in the China Sea - Hongmiao Pan; Kailing Zhu; Tao Song; Kui Yu‐Zhang; Christopher Lefèvre; Sue Xing; Min Liu; Sanjun Zhao; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2008)
Summary Magnetotactic bacteria are a heterologous group of motile prokaryotes, ubiquitous in aquatic habitats and cosmopolitan in distribution. Here, we studied the diversity of magnetotactic bacteria in a seawater pond within an intertidal zone at Huiquan Bay in the China Sea. The pond is composed of a permanently submerged part and a low tide subregion. The magnetotactic bacteria collected from the permanently submerged part display diversity in morphology and taxonomy. In contrast, we found a virtually homogenous population of ovoid‐coccoid magnetotactic bacteria in the low tide subregion of the pond. They were bilophotrichously flagellated and exhibited polar magnetotactic behaviour. Almost all cells contained two chains of magnetosomes composed of magnetite crystals. Intriguingly, the combination of restriction fragment length polymorphism analysis (RFLP) and sequencing of cloned 16S rDNA genes from the low tide subregion samples as well as fluorescence in situ hybridization (FISH) revealed the presence of a homogenous population. Moreover, phylogenetic analysis indicated that the Qingdao Huiquan low tide magnetotactic bacteria belong to a new genus affiliated with the α‐subclass of Proteobacteria . This finding suggests the adaptation of the magnetotactic bacterial population to the marine tide.

Identifying sources of groundwater in the lower Colorado River valley, USA, with δ18O, δD, and 3H: implications for river water accounting - Bradley E. Guay; Christopher J. Eastoe; R. Bassett; Austin Long (Hydrogeology Journal, 2006)

Temporal stability of aquatic food webs: partitioning the effects of species diversity, species composition and enrichment - Christopher F. Steiner; Zachary T. Long; Jennifer A. Krumins; Peter J. Morin (Ecology Letters, 2005)
Theory predicts that species diversity can enhance stability of community‐level biomass while simultaneously decreasing population‐level stability. Enrichment can theoretically destabilize communities but effects may become weaker with increasing diversity because of the inclusion of consumer‐resistant prey. Few experiments using direct manipulations of species diversity have tested these predictions. We used laboratory‐based aquatic food webs to examine the effects of species composition, diversity and enrichment on temporal variability of population‐ and community‐level biomass. We found weak effects of enrichment on population‐ and community‐level stability. However, diversity enhanced community‐level stability while species composition had no influence. In contrast, composition effects outweighed diversity effects when stability was measured at the population level. We found no negative effects of diversity on population‐level stability, in opposition to theory. Our results indicate that diversity can enhance stability in multitrophic systems, but effects vary with the scale of biological organization at which stability is measured.

Determination of Mercury Content in a Shallow Firn Core from Greenland by Isotope Dilution Inductively Coupled Plasma Mass Spectrometry - Jacqueline L. Mann; Stephen E. Long; Christopher A. Shuman; W. Robert Kelly (Water, Air, & Soil Pollution, 2005)

Human–environment interactions in South Florida's Everglades region: Systems of ecological degradation and restoration - William D. Solecki; John Long; Christine C. Harwell; Victoria Myers; Ezra Zubrow; Tom Ankersen; Christopher Deren; Camille Feanny; Richard Hamann; Lewis Hornung; Celeste Murphy; George Snyder (Urban Ecosystems, 1999)

Substrate preference of mycelium-bound lipase from a strain of Aspergillus Flavus Link - Kamariah Long; Hasanah M. Ghazali; Arbakariya Ariff; Yaakob Che Man; Christopher Bucke (Biotechnology Letters, 1998)

Nanoscale patchiness of bacteria in lake water studied with the spatial information preservation method - Christopher Krembs; Andrew R. Juhll; Richard A. Long; Farooq Azam (Limnology and Oceanography, 1998)
Direct evidence that free‐living bacteria can form small patches in the water column has been unavailable, despite long‐standing hypotheses, because traditional sampling methods destroy the aggregations. The recently developed spatial information preservation (SIP) method sufficiently preserves the two‐dimensional, relative spatial distribution of aquatic microorganisms to resolve patches on the scale of tens to hundreds of micrometers (nanoscale patchiness). We collected samples from lake water using the SIP method. Nanoscale patches were not found in several unmanipulated lake samples. However, we were able to stimulate patch formation by filtering out organisms larger than bacteria and adding freeze‐thawed diatoms. Patchiness developed within 3 h and then dispersed by 16 h after the addition of the algae. Patches did not form in an unfiltered sample that was rotated. The potential for free‐living aquatic bacteria to occur in patches has important implications for aquatic microbiology.

Susceptibility of potato varieties and advanced breeding lines (Solanum tuberosum L.) toPhytophthora infestans (Mont.) de Bary in greenhouse screenings - David S. Douches; William W. Kirk; Kazimierz Jastrzebski; Christopher Long; Ray Hammerschmidt (American Journal of Potato Research, 1997)

Effect of ambient temperature on the hypometabolic and hypothermic effects of sulfolane in rats - Christopher J. Gordon; Merritt D. Long; Robert S. Dyer (Archives of Toxicology, 1984)